Formulation and stability assessment of arabica and civet coffee extracts based cosmetic preparations - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Objective: The coffee is one of the most common beverages with reported health benefits. The coffee extracts are used in cosmetic and pharmacological preparations. The present study deals with the development of Arabica and Civet coffee extract based cosmetic formulas and its stability. Methods: Coffee extracts were prepared by mechanical pressing and solvent extraction methods. The total phenolic content of the extracts was assessed by Folin–Ciocalteu colorimetric method. The body lotion (BL) and hand moisturizing cream (HMC) were formulated, and the stability, heavy metal, and microbial contamination of the products stored at different temperatures for 3 months were evaluated by the organoleptic method, atomic absorption spectrophotometer, and plate assay, respectively. Results: The developed products (BL and HMC) were creamy, slightly dark in color with coffee fragrance. The products were stable, and no changes in color, odor, and texture were observed, for 3 months even at 40°C. BL was found to be not contaminated with lead, whereas, the presence of arsenic and mercury were found in the concentration of <0.16 and <0.09 mg/kg, respectively. The HMC has <0.16 mg/kg of arsenic and <0.09–0.28 mg/kg of mercury, while no lead content was detected. BL and HMC harbor only 253–281 and 231–251 CFU/g, respectively. The products were free from pathogenic microbes. The extract method has not affected the quality of the product. Conclusion: The BL and HMC were stable and contain negligible amount of heavy metal and found to be microbiologically safe. The presence of coffee extract in the products nourishes and protects the skin and suitable for topical applications.